Differential regulation of metalloproteinase production, proliferation and chemotaxis of human lung fibroblasts by PDGF, Interleukin-1β and TNF-α - Masahiro Sasaki; Masayuki Kashima; Takefumi Ito; Akiko Watanabe; Noriko Izumiyama; Masaaki Sano; Manabu Kagaya; Takanobu Shioya; Mamoru Miura (Mediators of Inflammation)
Fibroblast migration, proliferation, extracellular matrix protein synthesis and degradation,all of which play important roles in inflammation, are them selves induced by various growth factors and cytokines. Less is known about the interaction of these substances on lung fibroblast function in pulmonary fibrosis.